COMPUTER VISION BASED APPROACH FOR FOOD PACKAGING INSPECTION - Kadum, Juliet; Kadum, Amaal (International Journal of Psychosocial Rehabilitation, 2020)
This paper focuses on vision systems used in food packaging lines to ensure label accuracy, help manufacturers to fulfil safety regulations and avoid product recalls, whilst ensuring quality and improving efficiency. Throughout this paper, the term of machine vision ORC will refer to optical character recognition system, which is used for reading dates on food packaging with automated handling systems.